The Institutional Scholarship Program for Technological Development and Innovation as an Inducer of Intellectual Property at the Federal University of Sergipe - Santos, Maria dos Prazeres Costa (2025)
The general objective of the work is to evaluate the Programa Institucional de Bolsas de Iniciação em Desenvolvimento Tecnológico e Inovação (Pibiti) as an inductor of innovation at ​​Universidade Federal de Sergipe (UFS) The methodology performed in this study was exploratory in nature using both quantitative and qualitative approaches. The study works with a descriptive nature by identifying and describing characteristics in the development of the production of new technologies carried out by students with the guidance of professors at the UFS, the relationship between two variables, student and professor. Considerations to the Innovation and Intellectual Property Policy of the Universidade Federal de Sergipe carried out in order to encourage undergraduate students to exercise technological initiation and to register intellectual property assets that result in the technological aspects of startup creations, increase in assets of intellectual property and participation in notices of innovation and entrepreneurship.